2021
DOI: 10.1111/jocs.15625
|View full text |Cite
|
Sign up to set email alerts
|

Type A aortic syndromes in COVID‐19 positive patients: Case series from a UK multicentre study

Abstract: Objective The coronavirus disease (COVID‐19) increases the respiratory complications and carries a higher mortality in the immediate postoperative period. The aim of this study was to analyze the outcomes of patients with type A acute aortic syndromes (AAS) diagnosed with COVID‐19 in the perioperative period. Methods Retrospective analysis of prospectively collected data between March and August 2020 from 20 participating cardiac surgery centers in the United Kingdom. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…From these, 100 had the wrong population group or intervention, 105 reported the wrong outcomes, 56 were non‐observational studies and 29 in which the data were not extractable. Accordingly, a total of 18 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 articles fit the inclusion criteria and were included in our systematic review and meta‐analysis. This is outlined in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…From these, 100 had the wrong population group or intervention, 105 reported the wrong outcomes, 56 were non‐observational studies and 29 in which the data were not extractable. Accordingly, a total of 18 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 articles fit the inclusion criteria and were included in our systematic review and meta‐analysis. This is outlined in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that complications and mortality of cardiovascular emergencies and number of severe cases had been increased during the COVID‐19 pandemic 7,8 . Moreover, in another study, postoperative mortality was higher in COVID‐19 patients who needed cardiovascular surgery, compared to the patients without COVID‐19 9 . Type A aortic dissection in COVID‐19 patients seems to associate with increased severity that even with immediate and proper diagnosis, it has higher mortality.…”
Section: Discussionmentioning
confidence: 94%
“… 7 , 8 Moreover, in another study, postoperative mortality was higher in COVID‐19 patients who needed cardiovascular surgery, compared to the patients without COVID‐19. 9 Type A aortic dissection in COVID‐19 patients seems to associate with increased severity that even with immediate and proper diagnosis, it has higher mortality.…”
Section: Discussionmentioning
confidence: 98%
“…In the early phase of the pandemic during spring 2020, there were anecdotal observations of fewer patients presenting with acute aortic emergencies such as acute type A aortic dissection (ATAAD), though safe surgical repair has been described 2 . These observations were followed by numerous published studies revealing fewer emergency department presentations for acute myocardial infarction as well as greater rates of out‐of‐hospital cardiac arrest 3–10 . Additionally, in myocardial infarction patients specifically, there have been delayed presentations, slower rates to reperfusion, increasing frequency of post‐infarction mechanical complications, as well as greater rates of out‐of‐hospital death attributable to ischemic heart disease 7–11 .…”
Section: Introductionmentioning
confidence: 99%